Analysis of treatment costs for complex scalp wounds - Inhoff, Oliver Dirk; Faulhaber, Jörg; Rothhaar, Bärbel; Goerdt, Sergij; Koenen, Wolfgang (Journal der Deutschen Dermatologischen Gesellschaft, 2010)
Background: Two stage reconstructions of deep scalp wounds with exposed calvarial bone require a vital granulation tissue. By evaluating different surgical approaches functional and cosmetic results as well as economic aspects have to be taken into account. Patients and Methods: 52 patients undergoing three different surgical procedures for soft tissue reconstruction of complex scalp wounds with exposed bone were included into a retrospective study. All patients underwent a two stage procedure with 3D histologic control, soft tissue reconstruction and final split thickness skin grafting. Soft tissue reconstruction was carried out using allogenic fascia lata, an artificial skin substitute or a negative pressure wound therapy (NPWT). The costs for all used materials as well as personnel and infrastructure were calculated. Results: Comparing the costs for the different treatments, the fascia lata group was least costly (4,475 €) followed by the artificial skin substitute group (4,557 €). The highest expenses occurred in the NPWT group (7,.521 €). The artificial skin substitute group had the fewest dressing changes and the shortest treatment time. Conclusions: Although dermal regeneration templates are expensive, their use may be economic. NPWT causes high treatment costs due to high daily rental rates and frequent and time-consuming dressing changes.
First published: 22 October 2010
Gesehen am 28.06.2023